Makna Tradisi Pombaleana Bangka oleh Masyarakat Buton di Desa Labuan Beropa Kecamatan Laonti Kabupaten Konawe Selatan - Meldawati; La Niampe; Rahmat Sewa Suraya; Samsul (Jurusan Tradisi Lisan, Fakultas Ilmu Budaya, Univeritas Halu Oleo, 2023)
The Pombaleana Bangka tradition, is a tradition of lowering a ship that has just been made by builders and is ready to use. This tradition is an expression of gratitude from the Butonese people who are in Labuan Beropa Village for the sustenance given by the Almighty as well as a request for safety when using the ship. This research was conducted in Labuan Beropa Village, Laonti District, South Konawe Regency with the to describe the processes and meanings contained in the Pombaleana Bangka tradition. This study uses a type of qualitative research. Data collection through studies, documents, in-depth interviews and direct observation. Determination of informants using purposive sampling. The informants in this study were shipbuilders, village elders religious leaders and some people who know the Bombaleanan Bangka tradition. Data analysis techniques in this study consisted of four stages, namely data collection, data reduction, data presentation and conclusions. The results of this study indicate that (1) the process of carrying out the Bangka pombaleana tradition consists of several stages, namely, first patantuanan oeo malape or determining a good day, secondly bhatata pebahona Bangka or intention to bathe the boat, thirdly bubusina masina bathing the engine, fourth toloena loka, baana manu te aena manu or hanging bananas, chicken heads and feet, the five pasapona bangka or lowering the ship, the six haroa or praying and the seventh pekade-kande or eating together. (2) in the pombaleana tradition Bangka contains the meaning of material and the meaning of values of each process.